DEVELOPMENT OF ANDROID-BASED INTERACTIVE LEARNING MEDIA TO IMPROVE COGNITIVE LEARNING OUTCOMES DEMONSTRATING CAM SOFTWARE FRAISING MACHINERY - Muhammad Ifan Kurniawan; Muhammad Khumaedi (Jurnal Pendidikan Teknik Mesin, 2023)
This study aims to develop learning media so that it can be tested for feasibility, effectiveness, and practicality. This research was conducted using the Research and Development method. To determine valid and reliable learning media, a feasibility test was carried out by experts' assessment, and practicality according to students as users, then limited field trials used True Experimental Design with Simple two group research design Pre and Post Design. With the study population, namely students in class XII, the competence of expertise in Metal Fabrication and Manufacturing Engineering at SMK Negeri 7 Semarang consists of an experimental class and a control class, each class containing 30 students. The feasibility test results show that the media is very feasible to use. Data analysis used the t-test and N-Gain. Based on the results of the analysis it can be concluded that interactive learning media CAM milling machining is feasible to use, practicality tests in the very practical category are used and are more effective for improving student learning outcomes in learning CAM milling machining with an increase the average value is higher than the increase in the average value in the control class.